Effect Of Different Edge Preparations On The Tensile And Hardness Properties Of Gtaw Welded 6082 Aluminum Alloy. (2017) - Prasad, V.VARA; Lingaraju, D.
Abstract: Joining and welding are key enabling technologies for manufacture. The quality and reliability of a manufactured product are often determined by the quality of its joints. Aluminium alloy AA6082 find their greatest strength combined with good corrosion resistance, ease of formability and excellent ability to be anodized. Removing material along the edges of metal surfaces that are to be joined by welding is called a joint design or an edge preparation. These designs determine the penetration depth of the filler material in the weld joint. As the strength of a particular welded joint is related to the penetration depth achieved in a welded joint, edge penetration plays a pivotal role in determining the strength of the welded joint.In the present paper, different edge preparations of butt joints like single V, double V and single Y are fabricated on 6082 Aluminium alloy with different values of weld face openings. They are welded with GTAW with Al 4043 as a filler material. Tensile strengths of each weld is obtained and compared with different curve fitting equations.